Operational Cost Budget Optimization Analysis to Improve Efficiency of PT Citra Robin Sarana - Khairani, Umi; Rahmani, Nur Ahmadi Bi; Atika, Atika (Quantitative Economics and Management Studies, 2024)
The aim of the study is to assess the company's ability to optimize the operating cost estimates with the data for the period 2021-2023. A quantitative approach with multi-objective analysis is used, collecting data through interviews and analysis of administrative and financial data. The data used are secondary data from annual financial reports and data of operational costs as well as financial production data of the company. The results of the research showed the difference between the cost of budget and the costs of operational realization of the company: Rs. -161.525.511 in 2021, Rs. 1.530.471.758 in 2022, and Rs. 706.742.283 in 2023. Despite an increase from 2022 to 2023, operating costs are still not optimal. Efforts to optimize risk management have been seen, but have not achieved the expected results.